Regeneration time: ancient wisdom for planetary wellbeing. (24th September 2022) - Poelina, Anne; Wooltorton, Sandra; Blaise, Mindy; Aniere, Catrina Luz; Horwitz, Pierre; White, Peta J.; Muecke, Stephen
Abstract: In these regenerative times prompted by the Anthropocene, Aboriginal voices are situated to draw on ancient wisdom for local learning and to share information across the globe as ecological imperative for planetary wellbeing. In this paper, postqualitative research foregrounds the sentient nature of life as ancestral power and brings the vitality of co-becoming as our places into active engagement. It enables coloniality to surface and reveals how it sits in our places and lives, in plain sight but unnoticed because of its so-called common sense. Postqualitative research relates with ancient knowledges in foregrounding Country's animacy and presence, revealing the essence of time as non-linear, cyclical and perpetual. In this way, we are places, weather and climate, not separate. Postqualitative research also relates with ancient knowledge in illustrating Country as agentic and time as multiple, free of constraint and directly involved in our everyday. Country is active witness in the lives of Aboriginal peoples, here always. This is a strong basis for decolonisation. We all have a responsibility to listen, to help create a new direction for the future in the present time.